2015
DOI: 10.5539/elt.v8n8p31
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Receptive and Productive Vocabulary Sizes and their Increased Use by Azerbaijani English Majors

Abstract: This article reports on the results of two studies on receptive and productive vocabulary knowledge of first-year English majors in an English-medium degree programme. The aim of the study is to answer these research questions: (1) to what extent do the receptive and productive vocabulary sizes of English majors increase after a year of instruction; (2) what is the ratio between the increases in receptive and productive knowledge; (3) do English majors achieve the expected threshold vocabulary size of 4.000-5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The average receptive vocabulary is 6,775 words, whereas the average productive vocabulary is 4,006 words, indicating a difference of 27.69% between them. These results corroborate the findings of other researchers (Waring, 1997;Laufer, 1998;Webb, 2008;Zhou, 2010;Hajiyeva, 2014Hajiyeva, , 2015 and confirm that students' receptive vocabulary knowledge is higher than their productive vocabulary. In fact, the ESL first-year undergraduate engineering students displayed a higher average lexical knowledge compared to other ESL and EFL students examined in previous research articles reviewed in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The average receptive vocabulary is 6,775 words, whereas the average productive vocabulary is 4,006 words, indicating a difference of 27.69% between them. These results corroborate the findings of other researchers (Waring, 1997;Laufer, 1998;Webb, 2008;Zhou, 2010;Hajiyeva, 2014Hajiyeva, , 2015 and confirm that students' receptive vocabulary knowledge is higher than their productive vocabulary. In fact, the ESL first-year undergraduate engineering students displayed a higher average lexical knowledge compared to other ESL and EFL students examined in previous research articles reviewed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the average receptive vocabulary was 2,091 words, while the productive one comprised fewer than 1,000 words. In another study, Hajiyeva (2015) analyzed the relationship between receptive and productive vocabulary sizes and their use in an EFL context with a similar group. The results showed that the overall receptive vocabulary knowledge was broader than the productive knowledge and that the gap between them reduced after one year of instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, teaching vocabulary is a process of introducing, understanding, and bringing new words closer to students to use in communicating. Such as Aziz and Yamat (2016), Hajiyeva (2015), Mirta et al (2021) stated that teaching vocabulary aims to enable students to understand, acquire, and use foreign vocabulary for communicative purposes. Chang et al (2021), Deni and Fahriany (2020), Garwan and Priyanti (2021), Susanto (2017) stated that in teaching vocabulary teachers must remember that teaching vocabulary is a new and different lesson from the students' mother tongue.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Similarly, learners can understand the words while they are reading or listening (Alkhofi, 2015;Faraj, 2015;Maskor & Baharudin, 2016;Zhou, 2010) then also recalling the words (Hajiyeva, 2015) in RVK. Secondly, Nation (2001) and Hajiyeva (2015) also define RVK as passive vocabulary since outside stimuli could activate RVK. In short, if learners recognize a word when it appears in listening or reading texts, they may have receptive knowledge of that word.…”
Section: Receptive Vocabulary Knowledge (Rvk)mentioning
confidence: 99%